Measuring Productivity of Pesantren Cooperative using Malmquist Index - Solihah Sari Rahayu (SMART Insight, 2023)
This research aims to measure the level of productivity of Islamic boarding schoolcooperatives in Indonesia during the period from 2013 to 2021. The methodemployed in this study is the Malmquist Index Productivity (MPI). The researchfindings reveal fluctuations in the productivity trends of Islamic boarding schoolcooperatives from year to year. Furthermore, the study uncovers a significantdecrease in the level of productivity of these cooperatives during the Covid-19pandemic. The average productivity score of Islamic boarding schoolcooperatives throughout the research period indicates an overall decrease of0.614. This decrease is predominantly attributed to a decline in the averagetechnology change (TECHCH) with a value of 0.616 and a reduction in thechange in efficiency (EFFCH) with a value of 0.998. Individual analyses showthat Cooperative B exhibits the highest productivity value compared toCooperative A. However, both Cooperative A and Cooperative B are moresignificantly influenced by changes in efficiency in determining their productivitylevels